PEMBERDAYAAN MASYARAKAT DAN PENGELOLAAN AGROWISATA TELAGA MADIREDO SEBAGAI DESTINASI WISATA ALAM PEDESAAN - Muh Al Fatah Arief Putra; M. Bachtiar Affandie; Agung Winarno; Agus Hermawan (Rafandha Press, 2023)
The current tourism is certainly the primadonna sector, expected to become the locomotive for Indonesia's economic recovery. The Development of Tourism in the term of Agro-tourism in an area can help to increase the community and government income, if it is handled maximally. This activity aims to generate the potential in rural areas through empowerment and management activities of agriculture with tourism activities (agrotourism). Telaga Madiredo has the potential that can be developed as agro tourism destination in Malang Regency. This agrotourism development uses participatory rural appraisal (PRA) method using focus group discussion (FGD) techniques. The results of this service activity can be concluded that there is an understanding created regarding the marketing aspects of the offered tourism products, and an understanding of the duties and functions of the employees at Telaga Madiredo Agrotourism. This is proven with the diversion of marketing contents developed by Telaga Madiredo Agrotourism Managers. In addition, the community service team has succeeded in assisting the management of Telaga Madiredo Agrotourism in compiling the main tasks and functions that can be set as a reference to maximize the performance of the employees at Telaga Madiredo Agrotourism.